Characterising Rice Straw Ash: Unlocking the Potential of Agricultural Residues - Shah, Tejasi; Ray Chaudhuri, Ranjana; Soni, Udit; Shrivastava, Manoj; Venkatesh, G (Studia Ecologiae et Bioethicae, 2024)
Air pollution has become a scourge to contend with in India. The recorded concentrations of particulate matter (PM) in the atmosphere, the unabated emission of pollutants from vehicular exhausts, and recurring episodes of extremely poor condition (AQI>300) in the winter months, have rightfully and necessarily, spurred efforts in the industrial, governmental and research spheres to alleviate its detrimental impacts. Various point sources like biomass burning, coal combustion for power generation, and traditional agricultural practices such as stubble burning, collectively contribute to a steady rise in ambient particulate matter (PM) pollution. This study focuses on the utilization of rice straw – an abundant agricultural residue in a country like India – motivated by promoting and contributing to the soil-to-soil circularity paradigm. It encompasses the characterisation of straw ash from the rice, by delineating its physical properties, thermal characteristics, and chemical composition with the help of Thermogravimetric analysis (TGA), X-ray diffraction (XRD), Electron Probe Microanalysis (EPMA), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Dynamic Light Scattering (DLS). The results indicate that rice straw ash (RSA) possesses high silica content and favorable thermal stability. The RSA exhibited a porous structure, which enhances nutrient adsorption and microbial activity. Its incorporation into soil significantly improved soil nutrition and health, promoting a more sustainable agricultural practice. Entrenching this soil-to-soil thinking will contribute directly and indirectly to a host of sustainable development goals in a future Indian circular bioeconomy.